Hemato-biochemical parameters of Pesti-des Petits Ruminants (PPR) affected goats in Chittagong, Bangladesh - Bari, Md. Saiful; Rana, Eaftekhar Ahmed; Ahaduzzaman, Md.; Masud, Abdullah Al; Das, Tridip; Hasan, Tanjila (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The research work was aimed at assessing the prevalence and risk factors of Peste-des-petits-ruminants (PPR) in goats in some selected areas of Bangladesh along with a comparison of different hemato-biochemical parameters of PPR infected goats. Materials and methods: A presumptive diagnosis of PPR was done based on clinical signs and symptoms. A structured record keeping sheet was used for the estimation of prevalence and risk factors of PPR in goat. A total of 103 blood samples were collected randomly and analyzed for hemato–biochemical parameters using automated hemo-analyzer. Results: Out of 103 cases, Black Bengal (59%) and young goats aging minimum-12 months (43.85%) were recognized as highly susceptible to PPR disease. Strong association was found among all the three factors such as age, breed and sex (RR>1). All the values of hematological parameters such as TEC, TLC, Hb, PCV, and DLC were decreased in PPR affected goat as compared to healthy goats except lymphocyte counts, which was increased significantly (P=0.00). The amount of total protein (3.15 gm/L) and albumin (16.88 gm/L) were reduced drastically in PPR affected goats. Conclusion: The lymphocyte content in blood was significantly increased where as the total protein and albumin percent were decreased in the goats affected with PPR. Moreover, this variation in blood profile due to PPR virus infected in goat might be a good indicator in this disease diagnosis. http://doi.org/10.5455/javar.2018.e270